1282. Manogepix, the Active Moiety of the Investigational Agent Fosmanogepix, Demonstrates In vitro Activity Against Members of the Fusarium oxysporum and Fusarium solani Species Complexes. (31st December 2020) - Badali, Hamid; Patterson, Hoja; Sanders, Carmita; Mermella, Barbara; Gibas, Connie; Mele, James; Fan, Hongxin; Ibrahim, Ashraf S; Shaw, Karen J; Wiederhold, Nathan P
Abstract: Background: Invasive fusariosis is associated with marked morbidity and mortality in immunocompromised hosts, and treatment options are limited. Common etiologic agents include members of the F. oxysporum and F. solani species complexes (FOSC and FSSC, respectively). Manogepix (MGX), the active moiety of fosmanogepix, is a novel GWT1 inhibitor with broad antifungal activity. Fosmanogepix has previously shown in vivo efficacy in an immunocompromised murine model of invasive fusariosis. Our objective was to evaluate the in vitro activity of MGX against FOSC and FSSC isolates. Methods: Clinical isolates of FOSC (n=49) and FSSC (19) were identified by combined phenotypic characteristics and DNA sequence analysis of the translation elongation factor 1-alpha ( TEF1α ) and RNA polymerase II second largest subunit ( RPB2 ). Antifungal susceptibility testing was performed by CLSI M38 broth microdilution. Minimum effective concentrations (MEC) and minimum inhibitory concentrations (MIC) were read after 48 hours of incubation at 50% and 100% inhibition of growth for MGX, and MIC values were read for amphotericin B, posaconazole, isavuconazole, and voriconazole at 100% inhibition of growth. Results: MGX demonstrated potent in vitro activity against both FOSC and FSSC isolates. Against the 49 FOSC isolates, the MGX MECs ranged from < 0.015-0.03 mg/mL, and MICs at the 50% inhibition of growth endpoint ranged from < 0.015-0.12 mg/mL (Table). MIC values were higher when read at 100% inhibition of growth. Similar results were observed against FSSC isolates (MEC and MIC ranges < 0.015 and < 0.015-0.25 mg/mL, respectively). MGX MEC and MIC 50% inhibition values were in close agreement for both FOSC and FSSC isolates. Of the other antifungals tested, amphotericin B demonstrated in vitro good activity (MIC ranges 1-4 and 0.25-4 mg/mL against FOSC and FSSC, respectively). In contrast, the azoles demonstrated reduced susceptibility (MIC range 1- >16 mg/mL). MIC/MEC values (mcg/mL) for manogepix and other antifungals against FOSC and FSSC isolates Conclusion: MGX demonstrated in vitro activity against FOSC and FSSC clinical isolates. Both changes in fungal morphology (MEC) and reductions in growth (MIC 50% inhibition) were observed. Clinical studies are ongoing to determine the efficacy of fosmanogepix in patients with invasive fungal infections. Disclosures: Ashraf S. Ibrahim, PhD, Astellas Pharma (Research Grant or Support) Karen J. Shaw, PhD, Amplyx (Consultant)Forge Therapeutics (Consultant) Nathan P. Wiederhold, PharmD, Astellas (Grant/Research Support)BioMerieux (Grant/Research Support)Cepheid (Grant/Research Support)Covance (Grant/Research Support)F2G (Grant/Research Support)Gilead (Speaker's Bureau)Mayne Pharma (Advisor or Review Panel member)Sfunga (Grant/Research Support)